The effect of organizational socialization on creative behavior through the mediating role of employees’ well-being - علي رزاق جياد العابدي; شعيب احمد عزيز (Iraqi Journal for Administrative Sciences, 2024)
Objective and Purpose of Research : This study aims at identifying the effect of social and organizational formation on creative behavior through the intermediating role of employee’s well-being. Society and the entrance of the Research: The researcher has distributed 340 questionnaires to the new staff at the Directorate General for the Education of Babylon. The number of questionnaires returned was 324, of which 318 were valid for the statistical analysis and the response rate was 94% (Amos V.20) as well as the statistical program (SPSS V.20 (. The importance of the Research: The scarcity of the studies that attempted to determine and to know the nature of the relationship between the three variables of study (organizational socialization, employee wellbeing and creative behavior), as well as the current research attempted to address a real problem that directly affects the education sector in Iraq. Theoretical results: The presentation of the previous Studies showed a knowledge gap to explain the nature of the relationship between organizational socialization , the well-being of workers ,the creative behavior in the organizations in general and in the education of Babylon in particular. Practical results: There are two types of relationship between the variables of the study, which directly affect the relationship between social and regulatory development , the well-being of employees , the creative behavior. And other indirect between relationship organizational socialization ,the creative behavior through the intermediary role of the well-being of workers. The most important conclusions: The benefit and the gain of new employees in the Directorate General to raise Babylon from the practice of the Directorate of the process of socialization organizational will lead to desired behaviors the contributes to the achieve of the objectives of the organization, and reduces the cases of anxiety ,depression ,resentment , and the fear of work , Thus it improve their knowledge, skills, behavior, Well-being and a state of calm and serenity. Main Recommendations: The Directorate General of Education in Babylon Governorate continues to pay attention to the practices of organizational socialization and which have a great role in achieving the creative behavior and attention to factors that enhance the well-being of its employees.